Charakterisierung und Modellentwicklung von Natur und Funktionalität der Kathoden/Elektrolyt-Grenzfläche von Hochtemperatur-Brennstoffzellen (SOFC) - Szász, Julian Tibor (Schriften des Instituts für Angewandte Materialien - Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Angewandte Materialien - Werkstoffe der Elektrotechnik, 2019)
Solid oxide fuel cells (SOFC) achieve high efficiencies, the lower the internal electrochemical losses are. This work investigates insulating secondary phases at the cathode/electrolyte interface that are formed during fabrication. Full cells and model systems are electrochemically characterized, analyzed by electron microscopy and reconstructed by tomography. A FEM model reveals performance limiting factors. As a result, an optimized production routine is proposed.